The effect of Su Jok therapy to reduce the severity scale of physical complaints in diabetes mellitus patients: case reports - Octavia, Titin; Astuti, Reni Tri; Sutrisno, Ananda Prastuti; Nurjannah, Intansari (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2025)
Introduction: Diabetes mellitus is a chronic disease in the form of a metabolic disorder characterized by blood sugar levels that exceed normal limits. Diabetes mellitus patients may have physical complaints of pain, stiffness, numbness, and tingling that are usually related to the symptoms of diabetic neuropathy. This article aims to report the effect of Su Jok therapy on the severity scale of physical complaints in diabetes mellitus patients.Methods: This case report involved 15 respondents, and the data were collected in May 2023 at a public health center in Yogyakarta. Su Jok therapy was conducted by massaging with a probe for 5-10 minutes on the pain point found on the hands, and then followed by putting the fenugreek seeds with the sticky tape. Wilcoxon signed-rank tests were used for statistical analysis.Result: The report showed 13 respondents were female (86.7%) and 2 respondents were male (13.3%), with the largest number in the age range of 51-55 years and the age range of 61-65 years, as many as 5 respondents each (33.3%). A total of 19 types of physical complaints were found, with the most complaints being pain in both knees (26.67%). On a Likert scale of 1 to 5, where 1 represents no complaints and 5 represents extremely severe complaints, the average severity of physical complaints was 3.16 prior to therapy and 2.05 following therapy.Conclusion: Before and after Su Jok therapy, individuals with diabetes mellitus saw a substantial decrease in the severity scale of physical complaints (p=0.001, p<0.05). It may be stated that Su Jok combined with massage and fenugreek seeds, is a therapeutic approach that can help individuals with diabetes mellitus experience less severe physical problems.